KOMUNIKASI DAN KOORDINASI YANG SINERGI ANTARA PEMERINTAH DESA DAN BPD DALAM PEMBUATAN PERATURAN DESA - Paulina Dwijayanti E.42008061 (FISIP Universitas Tanjungpura Pontianak, 2012)
This writing is intended to determine the communication and coordination between the government of village and the village consultative bodies in drafting legislation for the welfare of rural people in Benuang village, Toho sub-district, Pontianak district.This study uses qualitative research type. Descriptive study aimed todescribe and analyze the relationship of synergy is the communication and coordination between the government of village and the village consultative bodies in villages in rural rulemaking of Benuang village. Research sites in the Benuang village, Toho sub-district, Pontianak district. Subject of study is the head of Benuang village and members of consultative bodies Benuang village and chairman, and secretary of Toho sub-district.Therefore, the recommendation in this research is by creating better communication and coordination and synergy between the tw and be awere of their positions as partners nt opponenets in achieving the formation of village regulations and fr the welfare of society.Keyword : Communication, Coordination, Sinergy, Village Regulations